SOUTH KOREAN GASTRODIPLOMACY STRATEGY IN IMPLEMENTING K-HALAL FOOD (KOREAN HALAL FOOD) IN INDONESIA IN 2012-2021 - Vita Kamila (UNIDA GONTOR, 2021)
In this research, the author discuss South Korea's strategy in implementing KHalal Food (Korean Halal Food) in Indonesia in 2012-2021. The purpose of thisresearch is to find out how South Korea uses its marketing strategy for K-Halal Foodin Indonesia to achieve its national interest in increasing the country's economy throughthe Halal food industry. This study uses the theory of gastrodiplomacy and the conceptof Halal Industry. This study used a qualitative method using a document-basedliterature study. The results of this research indicate that South Korea uses Halal foodto achieve its national interests in increasing exports of Halal food to Indonesia toincrease state revenues, by employing several strategies including; in collaborationwith Halal certification providers such as KMF (Korean Muslim Federation) and MUI(Indonesian Ulema Council). South Korea has also produced Korean drama to promoteK-Halal Food in Indonesia. In addition, from 2012 to 2021, South Korea is holding aK-Food Fair in Indonesia. With this gastrodiplomacy strategy, Indonesia and SouthKorea can improve their economies while also maintaining good relations between thetwo countries.